Methods for accurate high-temperature Sieverts-type hydrogen measurements of metal hydrides - Sheppard, Drew; Paskevicius, Mark; Javadian, P.; Davies, Ian; Buckley, Craig (ELSEVIER SCIENCE SA, 2019)
The potential of high-temperature metal hydrides (HTMHs) as thermal energy storage materials means that accurate assessment of their properties is required on the laboratory scale. Above ≃ 450 °C, the hydrogen permeability through sample cell reactors (SCRs) used in experiments to characterise HTMHs can have an appreciable impact on the data. In this work, the thermodynamic and kinetic properties of TiHx have been measured at temperatures up to 725 °C as a test of different practical methods for limiting the effects of hydrogen permeability and solubility in SCRs during high-temperature characterisation of metal hydrides. Aluminium-coated stainless steel and α-SiC were used to construct SCRs with reduced hydrogen permeability using commercially available techniques. When steel SCRs are the only practical option, guidelines have been developed to choose experimental conditions that minimise the effect on the data collected due to their hydrogen permeability and solubility. A method has also been developed to correct collected data for the hydrogen permeability and solubility of SCRs.